Sebuah PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI BERBASIS TPACK UNTUK MENINGKATKAN PENGUASAAN MUFRODAT - Arinda Avrillia Putri; Diva Fakih As Shkiy Thalib; Naifah Naifah; Atef Alshaer (UIN Sunan Gunung Djati Bandung, 2025)
The increasing demand for effective Arabic language instruction underscores the importance of innovative digital learning media in enhancing students’ vocabulary mastery and engagement. This study aims to develop animated video learning media based on the Technological Pedagogical Content Knowledge (TPACK) framework to improve mufrodat (Arabic vocabulary) mastery among tenth-grade students. The research employed a Research and Development (R&D) approach using the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation stages. The needs analysis revealed that conventional lecture-based instruction was ineffective, with 85% of students reporting boredom and difficulty memorizing vocabulary, and an initial mufrodat mastery level of only 30%. To address this issue, TPACK-based animated videos were developed through competency mapping, material structuring, and scriptwriting aligned with the integration of technology, pedagogy, and content. Expert validation results indicated high feasibility, with scores of 90.22% from media experts and 85.53% from content experts. The implementation was conducted with Grade X students at MA Darul Ulum Semarang. The effectiveness test demonstrated a significant improvement in learning outcomes, as the average score increased from 56.89 to 87.41, representing a gain of 30.52 points. Student responses (96.07%) and teacher observations (80.56%) further confirmed the high feasibility of the developed media. Overall, the findings indicate that TPACK-based animated video learning media are effective and engaging in improving students’ mufrodat mastery and learning outcomes, offering practical contributions to Arabic language education and digital learning innovation.